China Olympics and sponsor stocks. Issue 2 (6th September 2012) - Lee, Bob; Groves, David
This study examined the Olympic sponsors' stocks during the China 2008 Olympics to determine the impacts of a mega event such as Olympics on stock market value and its potential long–term influences. The study adapted a theoretical framework of the Built to Last and attempted to contextually and visually describe stock value changes of sponsor companies throughout the Olympic history. Stocks trend analysis method was used to analyse the charts of stock performance to determine if there were consistent patterns among chosen visionary companies such as Coca Cola, McDonalds, General Electric and Johnson & Johnson for the 2008 summer Olympics. The results of the study revealed that the uniqueness of each Olympic in its time and space. Among many variables that influenced sponsorship and its performance the most are a host country's culture, Olympic culture and the momentum of the Olympics.